PERANCANGAN SISTEM INFORMASI PENYEWAAN STUDIO MUSIK PADA WAYZON STUDIO MUSIK - Widyawati Widyawati; Ramdani Budiman; Andika Bayu Saputra; Anna Rosdiana (Jurnal Sistem Informasi dan Informatika (Simika), 2023)
Wayzon Studio Musik is one of the studios at seramg banten that provides two types of rentals, namely studio rentals and musical instrument rentals such as guitars, pianos, drums, basses, other musical instruments and sound systems. The studio rental system currently takes place by means of consumers registering directly on the spot and the recording process is carried out on a notebook and then continued with scheduling on the blackboard. the current system allows errors in the recording process, data loss, scheduling conflicts that often occur, the difficulty of finding information on music equipment rental services, the difficulty of managing transaction data and reports. based on the exposure to the current system, a studio rental system is needed that makes it easier to carry out the recording process, data search process, musical instrument rental, studio booking process and the process of finding information on music equipment rental services. This music studio rental system is designed using a codeigniter framework, bootstrap and a database management system (DBMS) using MYSQL. In this web development, the method used is the waterfall and Unified Modeling Language (UML). This system makes it easier and faster for administrative officers to provide scheduling information on studio and musical instrument rental services, minimizes errors in the process of processing transaction data and making reports and makes it easier for customers to find information on music equipment rental services. This system will display a monthly studio or musical instrument rental schedule (dashboard) and the report system will display transaction data that can be printed easily.